2002
DOI: 10.1074/jbc.m109440200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Glycogen Synthase Kinase-3 and Stimulation of T-cell Factor Signaling following Activation of EP2 and EP4 Prostanoid Receptors by Prostaglandin E2

Abstract: Recently we have shown that the FP(B) prostanoid receptor, a G-protein-coupled receptor that couples to Galpha(q), activates T-cell factor (Tcf)/lymphoid enhancer factor (Lef)-mediated transcriptional activation (Fujino, H., and Regan, J. W. (2001) J. Biol. Chem. 276, 12489-12492). We now report that the EP(2) and EP(4) prostanoid receptors, which couple to Galpha(s), also activate Tcf/Lef signaling. By using a Tcf/Lef-responsive luciferase reporter gene, transcriptional activity was stimulated approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
292
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 287 publications
(316 citation statements)
references
References 20 publications
18
292
3
3
Order By: Relevance
“…Furthermore, mice deficient in EP2 receptors exhibit a greater profibrotic response to bleomycin than wild-type mice, suggesting that changes in EP receptor profile can control in vivo fibrotic responses (36). Although we have clearly shown that EP2 and EP3 receptors are coupled to increases and decreases in cAMP, respectively, it remains possible that cross-talk among other downstream signaling intermediates, and/or transactivation of other receptors, may condition the response to PGE 2 and/or changes in cAMP (65)(66)(67)(68). Future studies will be directed at defining the precise explanation for our novel observations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mice deficient in EP2 receptors exhibit a greater profibrotic response to bleomycin than wild-type mice, suggesting that changes in EP receptor profile can control in vivo fibrotic responses (36). Although we have clearly shown that EP2 and EP3 receptors are coupled to increases and decreases in cAMP, respectively, it remains possible that cross-talk among other downstream signaling intermediates, and/or transactivation of other receptors, may condition the response to PGE 2 and/or changes in cAMP (65)(66)(67)(68). Future studies will be directed at defining the precise explanation for our novel observations.…”
Section: Discussionmentioning
confidence: 99%
“…9,43 It is worth mentioning that the transcriptional activity of b-catenin may also occur independent of the activation of Wnt and Fz. Activation of G protein-coupled receptors such as prostanoid (EP2, EP4), 44 lysophosphatidic acid (LPA2, LPA3), 18,45 gonadotrophin releasing hormone 46 and parathyroid 47 can also turn on b-cateninmediated gene transcriptional programs. In a recent study, it has been shown that the free G a and G bg subunits released from an activated G protein act co-operatively to inhibit b-catenin degradation and subsequently activate b-catenin-mediated transcriptional program.…”
Section: Canonical Wnt Pathwaymentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is involved in prostaglandin E 2 (PGE 2 ) synthesis and highly expressed in colon cancer (42,43). PGE 2 , through PKA and protein kinase B (PKB/AKT) activation, has also been shown to promote ␤-catenin signaling (44,45).…”
mentioning
confidence: 99%